Beginning REALbasic From Novice to Professional - Ford, Jerry Lee Jr (Apress : Imprint: Apress, 2006)
REALbasic is an easy-to-learn, powerful, cross-platform programming language, allowing you to write powerful applications that can be distributed across Windows, Mac, and Linux. This is a classic, no-fluff, tutorial-based book, ideal for: - Anyone wanting to master REALbasic - Anyone wanting to get into programming and produce their own applications easily and painlessly - REALbasic is very easy to pick up - Experienced VB programmers wanting an alternative, now that Microsoft have discontinued support for it. REALbasic is very similar to VB. - Any level of programmer wanting to create applications that can be ported to Windows, Mac, and Linux REALbasic's success is proven - there are already over 100,000 users, and this number is steadily growing. In a recent promotional effort, 35,000 Visual Basic developers downloaded a free copy of the Windows version of REALbasic, and REAL software has had many requests for decent beginning title on the subject. As far as we know, this is the only up-to-date book planned for the current version, REALbasic 2005, which matches that description. REAL software are enthusiastic about helping us sell the book.